Positioning and evaluation ... comparing my kampong.com and Wyne kiosks from customers perspective / Abdul Wahid Amit - Amit, Abdul Wahid (2005)
The study mainly captures on the positioning strategy of My Kampong • Com and Wyne kiosks at Kuching Waterfront based on their process and products attributes whereby the customers has to make perception and evaluation by comparing the attributes of both kiosks. At same time appropriate suggestion and recommendation are given to improve the present positioning strategy based on the attributes.